THE PROBABILITY OF CALCULATING THE POLLUTION LIMIT IN MINERAL-CONTAMINATED SOILS AND THE PHYSIOLOGICAL EFFECT OF THE SURROUNDING PLANTS - Estabraq Mohammed Ati, Rana Fadhil abbas , Zena Hassan Jazar , Dr. Reyam Naji Ajmi (Zeta Repository, 2023)
Pollution is a problem on a global scale that could have negative effects. In order to address this issue, it is important to take into account the primary sources of soil pollution, such as cemeteries. The primary goal of the current study was probability of calculating the pollution limit in mineral-contaminated soils and the physiological effect of the surrounding plants. Three fundamental sites the cemetery area and leaf Cupressus dupreziana .following three time periods of sampling, elements and factors such as (Pb ,Zn, Cd). Due to the site's exposure to soil disturbance, traceable elements were measured and chemically obtained using x-ray fluorescence (XRF). Samples were analyzed using ICPES for the qualitative detection of these elements after soil samples were digested for a control factor limiting the PTL threshold. The element's proximity to the sample is indicated by the relative proximity (RP), which is calculated by dividing the ICPES value on the XRF results of the sample. The component's biodegradability had a value at sites 2 and 1, respectively, and the highest value was discovered in areas 2 and 3. In the order Pb, Zn, and Cd, its plant absorption is 26%, 10%, and 7%. According to the data gathered, cemeteries have a significant potential to contaminate